2012
DOI: 10.1159/000342973
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Performance and Conversion to Alzheimer’s Disease in Early- Compared to Late-Onset Amnestic Mild Cognitive Impairment: CREDOS Study

Abstract: Background: Amnestic mild cognitive impairment (aMCI) is regarded as a prodromal stage of Alzheimer’s disease (AD). Given that patients with early-onset AD (EOAD) and with late-onset AD (LOAD) are known to have different clinical courses, symptoms and neuroimaging findings, early-onset (EOMCI) and late-onset aMCI (LOMCI) might be expected to have similar differences as EOAD versus LOAD. Methods: Our study involving 425 patients with aMCI (124 EOMCI, 301 LOMCI), who were followed for around 1.5 years, and 958 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 46 publications
5
25
0
Order By: Relevance
“…The mental control subtest of the Wechsler Memory Scale combined with RAVLT delayed recall was shown to have a classification accuracy of 89% in memory-impaired non-demented patients, two years before AD diagnosis [30]. Similarly, high predictive accuracy was found when combining episodic memory with naming [38,39] or verbal fluency [27,40,41]. Particularly high prediction values were obtained when combin-ing memory with more than one other domain.…”
Section: Cognition In Preclinical Admentioning
confidence: 96%
“…The mental control subtest of the Wechsler Memory Scale combined with RAVLT delayed recall was shown to have a classification accuracy of 89% in memory-impaired non-demented patients, two years before AD diagnosis [30]. Similarly, high predictive accuracy was found when combining episodic memory with naming [38,39] or verbal fluency [27,40,41]. Particularly high prediction values were obtained when combin-ing memory with more than one other domain.…”
Section: Cognition In Preclinical Admentioning
confidence: 96%
“…Mild cognitive impairment (MCI) is a clinical condition often associated with early stage of AD. A study of 425 MCI patients showed that early onset MCI patients suffer more visuospatial memory impairment, while a late onset of MCI showed more verbal memory problems; however, both are individual conditions at an increased risk of conversion to AD [106]. Moreover, other studies also reported no significant differences in the demographic characteristics of patients with mixed dementia and AD, where patients with mixed dementia were significantly more impaired than AD patients in global cognitive composite, attention and visuoconstruction [107].…”
Section: Sex Differences In Cognitionmentioning
confidence: 99%
“…Increased variability in neuropsychological performance in the old-old presents a unique challenge when diagnosing MCI, and individuals with early- versus late-onset MCI show differences in neuropsychological predictors of conversion to AD [12]. Furthermore, we have previously shown that the neuropsychological profiles associated with dementia detection in the very-old (mean age > 80 years) differ from those in the young-old (mean age < 70 years), with the very-old AD group outperforming the young-old AD group when age-adjusted standardized scores were applied, despite the groups achieving comparable raw scores [13].…”
Section: Introductionmentioning
confidence: 99%